Providing a conceptual model to design the municipal office space with an emphasis on the existential approach base on gegoraphical characteristic (Case study: Shahrekord city) - elham homayooni; elham pourmahabadian; sina razaghiasl (تحقیقات کاربردی علوم جغرافیایی)
The design of the work environment is directly linked to variations in construction performance. Factors that are not adequately considered in the design of the work environment may hinder the proper execution of administrative tasks, consequently leading to a decline in administrative productivity. The environmental characteristics of workspaces and their effects on employees are of particular significance. Furthermore, to enhance productivity within an organization, several conditions must be established, with the human factor being paramount; a motivated workforce is crucial for optimal performance. The primary objective of this research is to elucidate the optimal design model for municipal administrative spaces, with an existential approach influenced by the geography of Shahrekord. In this context, the research investigates the question of what constitutes the optimal model for designing municipal office spaces, informed by an existential perspective and geographical considerations unique to Shahrekord. The research employs a "descriptive-analytical" method for the theoretical foundation and a "survey method" for the presentation of findings. The environmental variables of office spaces, aligned with indicators of existential psychology, were assessed through a structured questionnaire. Upon completion of the questionnaires by the study participants, the collected data were analyzed using Amos and SPSS analytical software. The findings of this research regarding office buildings indicate that the most significant environmental parameters affecting human resource performance in office settings include color, lighting, noise pollution levels, visibility and scenery, indoor air quality, and thermal comfort. Additionally, factors such as design, flexibility, communication, workspace arrangement, furniture, and humidity can be categorized into two groups: psychological and physical components.